2010
DOI: 10.1039/c003573d
|View full text |Cite
|
Sign up to set email alerts
|

The role of structured water in mediating general anesthetic action on α4β2 nAChR

Abstract: Water is an essential component for many biological processes. Pauling proposed that water might play a critical role in general anesthesia by forming water clathrates around anesthetic molecules. To examine potential involvement of water in general anesthesia, we analyzed water within α4β2 nAChR, a putative protein target hypersensitive to volatile anesthetics. Experimental structurederived closed-and open-channel nAChR systems in a fully hydrated lipid bilayer were examined using all-atom molecular dynamics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 56 publications
(135 reference statements)
2
14
0
Order By: Relevance
“…The mechanism of this differential sensitivity to anesthetic agents between α4β2 and α7 nAChR is unclear. In previous studies using molecular dynamics simulations, Tang’s group found that, although multiple anesthetic binding sites were observed in α7, α4 and β2 subunits, anesthetic binding to a site at the interface between extracellular and transmembrane domains of the β2 subunit produced a profound change in protein dynamics that was likely to affect channel function [4245]. Based on these results, they proposed a hypothesis to explain the lower sensitivity of α7 nAChRs to general anesthetics, in which the susceptibility to anesthetic perturbation in the β2 (but not α7) subunit underlies the functional sensitivity of α4β2 nAChRs to volatile anesthetics [42].…”
Section: Significance Of the Heteromeric α7β2 Nachrmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism of this differential sensitivity to anesthetic agents between α4β2 and α7 nAChR is unclear. In previous studies using molecular dynamics simulations, Tang’s group found that, although multiple anesthetic binding sites were observed in α7, α4 and β2 subunits, anesthetic binding to a site at the interface between extracellular and transmembrane domains of the β2 subunit produced a profound change in protein dynamics that was likely to affect channel function [4245]. Based on these results, they proposed a hypothesis to explain the lower sensitivity of α7 nAChRs to general anesthetics, in which the susceptibility to anesthetic perturbation in the β2 (but not α7) subunit underlies the functional sensitivity of α4β2 nAChRs to volatile anesthetics [42].…”
Section: Significance Of the Heteromeric α7β2 Nachrmentioning
confidence: 99%
“…In previous studies using molecular dynamics simulations, Tang’s group found that, although multiple anesthetic binding sites were observed in α7, α4 and β2 subunits, anesthetic binding to a site at the interface between extracellular and transmembrane domains of the β2 subunit produced a profound change in protein dynamics that was likely to affect channel function [4245]. Based on these results, they proposed a hypothesis to explain the lower sensitivity of α7 nAChRs to general anesthetics, in which the susceptibility to anesthetic perturbation in the β2 (but not α7) subunit underlies the functional sensitivity of α4β2 nAChRs to volatile anesthetics [42]. To test this hypothesis, we examined the effects of isoflurane on native α7β2 nAChRs expressed in rat basal forebrain cholinergic neurons and heterologously expressed α7β2 nAChRs in Xenopus oocytes, and found that isoflurane significantly inhibited native α7β2 nAChRs on basal forebrain cholinergic neurons but did not inhibit native α7 nAChRs on ventral tegmental area (VTA) dopamine neurons [46].…”
Section: Significance Of the Heteromeric α7β2 Nachrmentioning
confidence: 99%
“…There are also observations that are incompatible with either of the above binding mechanisms, pointing to the critical role of water instead. 19-21 For instance, several studies have shown that anesthetic binding sites are amphipathic in nature, with possible accessibility to the aqueous phase. 22-24 There also exists a class of molecules, known as nonimmobilizers, that do not cause anesthesia at predicted concentration despite of their structure similarities to known anesthetics.…”
Section: Introductionmentioning
confidence: 99%
“…19-21 The close proximity of these water molecules to both protein surface and anesthetics suggests that the role of water in anesthetic-protein binding must be understood in conjunction with how water approaches the protein surface, i.e. the protein hydration process.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, three mutations in the TMD converted ivermectin from a positive into a negative allosteric modulator [148]. MD simulations using homology models of a7 and a4b2 nAChRs evidenced the importance of water mediation in the interaction of these receptors with anesthetics [151], and the higher affinity of halothane for the open form of a4b2 channels compared with the closed form [152]. In agreement with the experimental data, the a7 channels present an opposite behavior, with a higher affinity for the closed form and unresponsive correlated motions which explain the functional insensitivity of this nAChRs subtype to volatile anesthetics [153].…”
Section: Transmembrane Domain Of Nachrsmentioning
confidence: 99%